Influence of Hip Mobility and Strength on Gait Parameters among Young Females—A Cross-Sectional Study - Alagingi, Nityal Kumar; Salin, Deekshitha (Journal of Health and Allied Sciences NU, 2023)
Background The hip's primary function is to dynamically support the weight of the trunk while allowing the force and load transmission axial skeleton to the lower extremity and henceforth allowing mobility. The function of the hip is not only to take the load of the trunk to the lower extremity but also to perform daily activities which include walking, running, jumping, sitting, etc. Hip muscle strength is required to stabilize the pelvic and trunk during squatting and walking (single stance) and to perform other daily living activities. The prevalence rate reports that males are more physically active than females. The number of physical activities has shown to be decreased in teens and young adults between the ages of 14 and 22 years due to transitions in their lifestyle. These changes can be behavioral and due to body composition. The objectives of the study are to determine the influence of hip mobility and strength on the spatial and temporal parameters of gait.Methodology This is a cross-sectional study involving a total of 50 young female populations that have been selected based on the inclusion criteria. Hip range of motion using a universal goniometer was measured in three trials with 30 seconds of rest between each measurement. The hip muscle strength was measured using a handheld dynamometer with 5 seconds hold and three trials taking 30 seconds of rest between each measurement. Spatial parameters of gait were measured by using Kinovea software V.0.8.15, and temporal parameters of gait were measured by asking the subject to walk comfortably in their own speed for 1 minute and the video was taken and measured.Result The hip internal rotation and external rotation has shown to have a statistical significance with spatial and temporal parameters of gait. The hip abductors, adductors, internal rotators, and external rotator muscle strength have shown to have statistical significance with spatial and temporal parameters of gait. Descriptive statistics were used for demographic characteristics, and Pearson's correlation coefficient is used for determining association between outcome variables.Conclusion The hip abductors, adductors, internal rotators, and external rotators have shown to have influence on gait parameters specially with walking speed. The hip internal and external rotation has shown to have influence on gait parameters.
Keywords: influence; hip mobility; muscle strength; parameters of gait